A New Bent-toed Gecko (Cyrtodactylus: Squamata: Gekkonidae) from the Island of Tanahjampea, South Sulawesi, Indonesia - Riyanto, Awal; Hamidy, Amir; Mcguire, Jimmy A. (Zootaxa, 2018)
The recent description of Cyrtodactylus tahuna from Sangihe Island and descriptions of other new species from remote islands in the Indo-Australian Archipelago indicate the important role of oceanic dispersal and isolation in the evolution and diversification of the genus Cyrtodactylus. We provide another example involving Tanahjampea Island, a remote island 155 km south of the Southwestern Peninsula of Sulawesi, Indonesia. Here, we describe a new species on the basis of 11 specimens collected from that island. This new species is an intermediate sized Cyrtodactylus with a snout–vent length of up to 76.1 mm in adult males and 72.8 mm in females. It is easily distinguished from all recognized species occurring on Sulawesi as well as in the Moluccas and Lesser Sunda Islands by the following unique combination of characters: (1) brachium and antebrachium tuberculated, (2) ventrolateral folds with tubercles, (3) 20–23 irregularly aligned rows of keeled tubercles, (4) 31–34 paravertebral tubercles, (5) 29–34 ventral scales between ventrolateral folds, (6) no precloacal depression, (7) enlarged precloacofemoral scales in continuous series, (8) males with 20–24 precloacofemoral pores in wide Ʌ-shape, (9) enlarged post precloacal scales present, (10) 19–21 fourth toe subdigital lamellae, (11) enlarged transversely median subcaudals absent, (12) tail not prehensile, (13) tubercles extend along 71% of original tail length, and (14) the original tails reaching 147% of snout–vent length. We also provide an identification key to the bent toed gecko species that occur in the Wallacea region.